2008
DOI: 10.1017/s1751731107001115
|View full text |Cite
|
Sign up to set email alerts
|

Variance and covariance components for liability of piglet survival during different periods

Abstract: Variance and covariance components for piglet survival in different periods were estimated from individual records of 133 004 Danish Landrace piglets and 89 928 Danish Yorkshire piglets, using a liability threshold model including both direct and maternal additive genetic effects. At the individual piglet level, the estimates of direct heritability in Landrace were 0.035, 0.057 and 0.027, and in Yorkshire the estimates were 0.012, 0.030 and 0.025 for liability of survival at farrowing (SVB), from birth to day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 18 publications
5
31
4
1
Order By: Relevance
“…Few studies have differentiated between a sire and dam line, and none of them originating from the same breed . Studies analysing and comparing different breeds showed that there are clear differences in genetic parameters between breeds (See et al, 1993;Roehe and Kennedy, 1995;Su et al, 2008). Only a few studies (Ferraz and Johnson, 1993;Hermesch et al, 2000c;Serenius et al, 2004b) have used data from Large White pigs in their studies to compare different breeds, and none of these studies differentiated between sire and dam line within the breed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have differentiated between a sire and dam line, and none of them originating from the same breed . Studies analysing and comparing different breeds showed that there are clear differences in genetic parameters between breeds (See et al, 1993;Roehe and Kennedy, 1995;Su et al, 2008). Only a few studies (Ferraz and Johnson, 1993;Hermesch et al, 2000c;Serenius et al, 2004b) have used data from Large White pigs in their studies to compare different breeds, and none of these studies differentiated between sire and dam line within the breed.…”
Section: Discussionmentioning
confidence: 99%
“…Generally estimates for the maternal genetic effects in these studies are higher than the direct genetic effect (Grandinson et al, 2005;Rydhmer et al, 2008;Su et al, 2008). In this study, survival as SB was analysed at sow level, since individual piglet information was not available.…”
Section: Reproduction Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Campbell (1997) found low and non-significant genetic correlation between seedling emergence and survival to flowering in a monocarpic herb Scarlet Gilia (Ipomopsis aggregata). Studies on piglet mortality from farrowing to weaning around 4 weeks of age have found close to zero or even negative genetic correlations between different periods, thus suggesting that different piglet survival traits do not share a common genetic background and should be treated as separate traits (Su et al, 2008, and references therein). Ducrocq et al (2000) found that survival of laying hens during rearing (from birth to housing at 106 days) and productive periods (from housing to 313 days of age) are genetically different traits with different mortality rates and genetic correlation close to zero.…”
Section: (I) Survival Within Fingerling Stagementioning
confidence: 99%
“…Low heritability of survival has been found in diverse taxonomic groups in farmed terrestrial animals (e.g. van Arendonk et al, 1996;Ducrocq et al, 2000 ;Knol et al, 2002;Goyache et al, 2003 ;Casellas et al, 2007 ;Su et al, 2008) and in wild organisms (e.g. Futuyma et al, 1995;Campbell, 1997).…”
Section: (Iii) Factors Causing Weak Correlations Between Life Stagesmentioning
confidence: 99%